Peace a novel - Bausch, Richard 1945- (Vintage contemporaries, 2009)
Italy, near Cassino. The terrible winter of 1944. A dismal icy rain, continuing unabated for days. Guided by a seventy-year-old Italian man in rope-soled shoes, three American soldiers are sent on a reconnaissance mission up the side of a steep hill that they discover, before very long, to be a mountain. And the old man's indeterminate loyalties only add to the terror and confusion that engulf them on that mountain, where they are confronted with the horror of their own time--and then set upon by a sniper.--From publisher description